(untitled) (Global Journal of Human-Social Science, 2026)
The implementation of communication strategies and tactics within the Russian-language extremist discourse utilizes a range of specific linguistic means. These primarily include lexical and semantic units that substantiate extremist doctrines and shape the images of "victim" and "enemy." In addition to lexical and semantic units, other linguistic means are also used: word-formation (e.g., suffixes and prefixes of nouns with connotations of disapproval or disdain); morphological (various instances of violation of grammatical usage); syntactic (exclamatory sentences, ellipsis, inversion, etc.); stylistic (metaphor, metonymy, synecdoche, allegory, hyperbole, litotes, etc.). In this work, we will characterize the lexical (lexical-semantic), syntactic, and stylistic devices that most influence the formation of the speech profile of a Russian-speaking extremist.